THE TEAM SPORT OF CONFRONTATION AS A SPACE OF TRANSGRESSION OF FEMININE IDENTITY (Fiep Bulletin - online, 2014)
The present study has an as objective to go deeper into the debate about the participation of adolescents in the oriented sports and leisure universe, having as its main focus to analyze the different choices and ways in which adolescents can represent themselves in confrontation sports such as basketball, handball and indoor soccer as those are sports that men normally are predominant. According to Giddens (2002) and Woodard (2005) on the concepts of identity and modernity, and to the historical analysis of Mourao (1996), among others, on female participation in contact sports, we intend to review the idea of males taking advantage of confrontation sports to impose themselves over females in the early phases of in school socialization. A survey from a public source on the practice of leisure in a multi sport social project, done with people from all ethnic groups from that same location, model chosen for its intention to "trace a curve in a social speech, and fix it in a non inspectional form" (GEERTZ, 1998), at the end of basic schooling (middle school) it was observed a growth in the number of females involved in sports in general, and specifically in sports where males tend to be predominant. The results that have been checked till this point, compared with other similar studies about the involvement of adolescents in male predominant sports reveal the major influence that physical education classes have in the development of new identities, in the level of participation and in promoting diversity in gender in sports and other leisure activities in modern days.
Keywords: team-confrontation sports; female adolescents; oriented leisure